Observer‐based adaptive consensus tracking for linear multi‐agent systems with input saturation. Issue 14 (1st September 2015) - Chu, Hongjun; Yuan, Jingqi; Zhang, Weidong
Abstract : This study considers the observer‐based consensus tracking problem of linear multi‐agent systems with input saturation. Existing observer‐based consensus protocols are designed based on an undirected graph, and need global information, such as the network size or eigenvalue information of the Laplacian matrix. In this study, based on only the agent dynamics and the relative outputs of neighbouring agents, an adaptive consensus protocol is proposed by assigning a time‐varying coupling weight to each node, and this protocol is independent of any global information and hence is fully distributed. Under the assumptions that each agent is asymptotically null controllable with bounded controls and detectable, and the topological graph has a directed spanning tree with the leader as the root node, semi‐global observer‐based consensus tracking of multi‐agent systems can be reached despite actuator saturation occurring. The results are applied to consensus tracking control of two‐mass‐spring systems, which are well‐known models for vibration in many mechanical systems.